Combinatorial synthesis of BaTiO3–Bi(Mg2/3Nb1/3)O3 thin-films for high-temperature capacitors. (13th April 2015) - Kumaragurubaran, Somu; Nagata, Takahiro; Takahashi, Kenichiro; Ri, Sung-Gi; Tsunekawa, Yoshifumi; Suzuki, Setsu; Chikyow, Toyohiro
Abstract: Combinatorial thin-film of (1− x )[BaTiO3 ]– x [Bi(Mg2/3 Nb1/3 )O3 ] — (BT–BMN) was grown on Pt/Ti/SiO2 /Si, using pulse laser deposition (PLD) method, by ablating stoichiometric and Bi-10 wt % enriched targets to optimize the Bi content. X-ray photoelectron spectroscopy analysis revealed a linear Bi composition spread. As-deposited films post-annealed at high-temperatures, under oxygen atmosphere, turned into crystalline state. The crystallinity, characterized by X-ray diffraction, is better towards Bi-enriched region. The dielectric constant showed a strong dependency of Bi composition and saturated over Bi-7 wt %. The scanning nonlinear dielectric microscopic investigation revealed ferroelectric phase distribution is better around Bi-7 wt % region where the measured leakage current is also minimum. Dielectric constant over 240 and dielectric constant stability below 13% (25–400 °C range) were obtained.